MODELING POSSIBILITY OF UTERINE BLEEDING PUBERTY IN GIRLS DEPENDING ON THE CHARACTERISTICS OF SONOGRAPHIC PARAMETERS UTERUS AND OVARIES AND HORMONAL BACKGROUND IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE - Chaika, G.V.; Prokopenko, S.V.; Kucherenko, O.M. (World of Medicine and Biology, 2015)
Aim of our work - to build a discriminant models for forecasting the risk of uterine bleeding puberty in girls depending on the characteristics of sonographic parameters of uterus and ovaries and hormonal levels in the different phases of the menstrual cycle.Materials and methods. Initial sonographic parameters of uterus and ovaries and also hormonal levels in follicular and luteal phases of the menstrual cycle in 113 healthy girls aged from 14 to 15 years and 121 girls aged from 16 to 18 are taken from the database of materials Scientific and Research Center Vinnitsa National Medical University named after Pirogov. On the bases of the Vinnytsya City Clinical Hospital, Vinnitsa city maternity hospital № 1 and Vinnytsya Central Regional Hospital carried out sonographic study of uterus and ovaries (using ultrasound machine "Vivid 7" firm QE Mtdical Sysnems, USA), and indicators of hormonal status (luteinising, follicle stimulating, prolactin, thyroid stimulating, estradiol, progesterone and testosterone using commercial kits of reagents for the study of hormone levels in blood plasma) in 18 girls aged from 14 to 15 years and 48 girls aged from 16 to 18 years with pubertal uterine bleeding in the different phases of the menstrual cycle. All of them anthropometric survey carried out by scheme of Bunak; somatotype determine by the method of J. Carter and B. Heath; component composition of body weight by methods J. Matiegka, the American Institute of Nutrition and WE Siri.Construction of discriminant models of risk of development bleeding puberty held in license statistical package "STATISTICA 6.0".Results. DiscussionsDeveloped on the basis of sonographic parameters of uterus and ovaries and hormonal levels in the different phases of the menstrual cycle discriminant model allow to predict the possibility of pubertal uterine bleeding in girls of 14-18 years (99.1% correct in cases, statistics Wilks lambda = 0.118, p
Keywords: pubertal uterine bleeding; sonography of uterine and ovarian; hormones; discriminant model